Method for recycling metal in waste photovoltaic welding strip

The precipitation of metal hydroxide by hydrochloric acid treatment and control of pH value is generated, and then chloride is generated and perovskite materials are prepared, which solves the problem of low resource utilization efficiency of waste photovoltaic welding tape, realizes efficient separation and resource utilization, and reduces environmental pollution.

CN120230914APending Publication Date: 2025-07-01JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510431501.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-08
Publication Date
2025-07-01

AI Technical Summary

Technical Problem

In the prior art, the resource recycling efficiency of waste photovoltaic welding tape is low, and more harmful substances are generated during the recycling process, resulting in environmental pollution and waste of resources.

Method used

The photovoltaic solder tape samples were treated with hydrochloric acid, and the hydroxide precipitation of different metals was generated by controlling the pH value, and separated them. Then, dilute hydrochloric acid was used to generate aluminum chloride and lead chloride/tin chloride, and finally, the lead-based/tin-based perovskite material was prepared with organic amines.

Benefits of technology

The efficient separation and resource utilization of metals in waste photovoltaic welding tapes has been achieved, which reduces environmental pollution, improves resource recycling rate, and prepares economical aluminum-based flocculants and halogen perovskite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120230914A_ABST
    Figure CN120230914A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy recycling treatment, and particularly relates to a method for recycling metal in a waste photovoltaic welding strip, which comprises the following steps of: 1, disassembling and calcining the photovoltaic welding strip to obtain a fine blocky photovoltaic welding strip sample; 2, processing the photovoltaic welding strip sample by using hydrochloric acid, and separating a copper bar from filtrate; 3, adding a hydroxide solution to adjust the pH value of the filtrate obtained in the previous step, sequentially generating hydroxide precipitates of aluminum, lead and tin from low to high, and separating for later use; 4, dissolving the aluminum hydroxide precipitate in diluted hydrochloric acid again to generate aluminum chloride, and extracting the aluminum chloride to be used as an aluminum-based flocculant after full reaction; and 5, respectively synthesizing the lead hydroxide precipitate and / or the tin hydroxide precipitate into a corresponding lead-based perovskite material and / or a tin-based perovskite material. According to the method, the metal substances of the photovoltaic welding strip can be effectively recycled, and the product is novel, less in pollution and economical.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of new energy recycling and treatment, and specifically relates to a method for the resource recycling of metals in waste photovoltaic solder tapes. Background Art

[0002] With the rapid development of the solar photovoltaic industry, solar power generation has become a key force in the global green energy transformation and is widely used in various fields such as households, industries, and commerce. As a renewable energy source, solar photovoltaic power generation can not only effectively reduce the dependence on fossil fuels but also significantly reduce greenhouse gas emissions, contributing to the global response to climate change. Currently, the service life of solar cells in the market is 20 to 30 years. However, as the service life increases, the conversion efficiency of photovoltaic modules will gradually decline, ultimately resulting in the inability of photovoltaic panels to continue generating electricity effectively. According to relevant predictions, China will enter the peak period of photovoltaic module scrapping around 2025, and a large number of waste photovoltaic panels will face disposal problems at that time. How to scientifically and reasonably recycle and reuse these retired photovoltaic modules, reduce environmental pollution caused by waste, and at the same time achieve efficient recycling of resources has become an urgent issue to be solved.

[0003] The recycling of waste photovoltaic modules is not only an environmental issue but also a resource issue. Photovoltaic panels contain various recyclable precious metal materials such as silver, copper, aluminum, and silicon, which have high economic value in the photovoltaic industry. If these metal materials are not effectively recycled, it will inevitably cause a waste of precious resources. At the same time, the waste photovoltaic solder tapes may also contain harmful substances such as lead. If not properly treated, these harmful substances will penetrate into the soil and water sources, causing long-term pollution to the ecological environment. Therefore, the development of efficient, economical, and environmentally friendly photovoltaic module recycling technologies has become an urgent task.

[0004] Materials such as the aluminum frames, silicon solar cells, copper, tin, lead, and precious metal silver in photovoltaic modules all have significant recycling value and economic potential. Metals such as aluminum and copper can be reused in multiple industrial fields, and the recycling of solder tapes and silicon solar cells can effectively reduce the demand for natural resources and the environmental burden. Reasonable recycling and treatment can not only effectively extract these valuable metals, improve the recycling efficiency of resources, but also reduce the negative impact of waste on the environment and prevent the release of harmful substances. In this regard, we propose a method for efficiently recycling some metals in photovoltaic solder tapes, which can maximize the recovery of precious metals and other metal materials, improve resource utilization efficiency, and reduce environmental pollution at the same time. Summary of the Invention

[0005] The purpose of the present invention is to provide a method for the resource recycling of metals in waste photovoltaic solder tapes to solve the technical problems of low recycling efficiency of resources and the generation of more harmful substances during the recycling process in the prior art.

[0006] The method for recycling metal resources in waste photovoltaic welding ribbons comprises the following steps.

[0007] 1. Disassembly and calcination of photovoltaic welding ribbons to obtain small block-shaped photovoltaic welding ribbon samples;

[0008] 2. Treat the photovoltaic ribbon samples with hydrochloric acid to separate the copper strips and the filtrate;

[0009] 3. Adding a hydroxide solution to adjust the pH value of the filtrate obtained in the previous step, generating hydroxide precipitates of aluminum, lead and tin at specific pH values ​​in order from low to high, and separating the precipitates in order for later use;

[0010] 4. Dissolving the aluminum hydroxide precipitate in dilute hydrochloric acid again to generate aluminum chloride, and extracting the aluminum chloride after sufficient reaction to use as an aluminum-based flocculant;

[0011] 5. Dissolve the lead hydroxide precipitate and / or the tin hydroxide precipitate in dilute hydrochloric acid again to generate lead chloride and / or tin chloride, use the lead chloride and / or tin chloride as lead source and tin source, respectively, and then react the lead source and / or tin source with organic amine to synthesize the corresponding lead-based perovskite material and / or tin-based perovskite material.

[0012] Preferably, in step one, the waste photovoltaic panels are first disassembled manually or mechanically to remove the aluminum frame and the junction box to obtain a cell assembly; the disassembled cell assembly is then calcined in a muffle furnace at a certain temperature for a certain time to obtain silicon wafers and photovoltaic welding strips; the photovoltaic welding strips are pre-processed into small blocks for subsequent processing.

[0013] Preferably, in step two, the pretreated photovoltaic ribbon sample is placed in a hydrochloric acid solution according to a certain solid-liquid ratio, and reacted at a certain temperature. The solid-liquid ratio between the photovoltaic ribbon sample and the hydrochloric acid solution is in the range of 1:10-25, the concentration of the hydrochloric acid solution is in the range of 2-5M, the reaction temperature is in the range of 50-70°C, and the reaction time is in the range of 1-3h.

[0014] Preferably, in step three, the pH value of the filtrate is adjusted to pH=5 to generate aluminum hydroxide precipitate, and the aluminum hydroxide precipitate is separated; the pH value of the filtrate is adjusted to pH=8 to generate lead hydroxide precipitate, and the lead hydroxide precipitate is separated; the pH value of the filtrate is adjusted to pH=10 to generate tin hydroxide precipitate, and the tin hydroxide precipitate is separated.

[0015] Preferably, in step three, the hydroxide precipitates of aluminum, lead and tin are separated from the filtrate by centrifugal separation, and the separated metal hydroxide precipitates can be further washed with hydrochloric acid once and multiple times.

[0016] Preferably, in step two, during the reaction, samples are taken every 30 minutes to observe the dissolution situation. Each time, 10 mL of the solution is taken out, and a total of 2 - 5 samplings are carried out.

[0017] Preferably, in step one, the calcination temperature is 500 °C, the calcination time at 500 °C is 30 minutes, the heating-up time is set to 100 minutes, and the heating rate is 5 °C / min.

[0018] Preferably, in step five, the preparation method of the reaction between lead chloride and organic amine includes the microwave method. First, Cs2CO3, PbCl2, diethylene glycol butyl ether, octadecene, oleic acid, and oleylamine are respectively put into a microwave bottle; then, after adding a magnetic stir bar, it is put into a microwave instrument, and a microflake containing CsPbCl3 nanocrystals is synthesized by the method of programmed temperature rise; when the sample cools to 71 °C, the microwave bottle is taken out of the microwave instrument and cooled to room temperature with ice water. After centrifugation, the solid is retained.

[0019] The HCl solution used in the present invention is an effective metal leaching solution and does not require the addition of other oxidants. It is a suitable leaching solution for the wet leaching of waste photovoltaic solder strip materials. The scheme of selecting the HCl solution as the leaching solution and adjusting the pH with sodium hydroxide to purify metal ions step by step also has the following advantages:

[0020] Novel product: In the prior art, there is a lack of technology for directly recycling and manufacturing aluminum-based flocculants and halide perovskite materials from waste photovoltaic solder strip materials.

[0021] Less pollution: HCl is used to selectively obtain precipitates of three different metal hydroxides, aluminum, lead, and tin. Then, by treating with the HCl solution, aluminum chloride flocculant, and lead source and tin source for preparing halide perovskite materials, lead chloride and tin chloride, can be directly obtained. Since the same HCl solution is also selected for the leaching solution, the treatment of the precipitate can be relatively simple, and no other chemical reagents are required except for impurity removal treatment, resulting in less pollution.

[0022] Economy: Hydrochloric acid and sodium hydroxide are relatively cheap and easily obtainable chemical reagents. Compared with other solvents or complex chemical reagents, their usage costs are lower. In addition, the process does not require overly complex equipment or operation steps, facilitating large-scale industrial application and having good economy.

[0023] High selectivity: The solubilities of hydroxides of different metal ions are different. By controlling the pH value of the solution, certain metal ions can be selectively precipitated.

[0024] Complete precipitation: Under appropriate conditions, sodium hydroxide can react completely with metal ions in the solution to form precipitates, ensuring the complete separation of metal ions. By multiple precipitation and washing steps, the purity of the precipitate can be further improved.

[0025] Resource utilization: The separated aluminum ions, lead ions, and tin ions are further utilized for resource recovery respectively. The aluminum ions are synthesized into aluminum-based flocculants, and the lead ions and tin ions are respectively synthesized into halide perovskite materials. Description of the Drawings

[0026] Figure 1 This is the basic flowchart of the method for resource recycling of metals in waste photovoltaic solder tapes in the present invention.

[0027] Figure 2 This is a schematic diagram showing the change of aluminum leaching rate with time in 5M hydrochloric acid in the present invention.

[0028] Figure 3 This is a schematic diagram showing the change of lead leaching rate with time in 5M hydrochloric acid in the present invention.

[0029] Figure 4 This is a schematic diagram showing the change of tin leaching rate with time in 5M hydrochloric acid in the present invention.

[0030] Figure 5 This is the XRD pattern of the solder tape after reaction in 2 - 6M hydrochloric acid in the present invention. Detailed Embodiments

[0031] The following is a more detailed description of the specific embodiments of the present invention with reference to the drawings and through the description of the examples, in order to help those skilled in the art have a more complete, accurate and in-depth understanding of the inventive concept and technical solution of the present invention.

[0032] As Figures 1-5 shown, the present invention provides a method for resource recycling of metals in waste photovoltaic solder tapes, including the following steps.

[0033] I. Disassembly and calcination treatment of the photovoltaic solder tape to obtain small blocky photovoltaic solder tape samples.

[0034] This step includes:

[0035] First, the waste photovoltaic panel is manually or mechanically disassembled to remove the aluminum frame and junction box to obtain the cell module.

[0036] Then, the disassembled cell module is calcined at a certain temperature in a muffle furnace for a certain time to obtain silicon wafers and photovoltaic solder tapes. The calcination temperature is 500°C, the calcination time at 500°C is 30 min, the set heating time is 100 min, and the heating rate is 5°C / min.

[0037] The photovoltaic solder tape is pretreated into small blocks for subsequent treatment. The obtained product is small blocky photovoltaic solder tape samples. The purpose of pretreating the photovoltaic solder tape into small blocks is to increase its surface area, greatly increase the contact area between the solder tape and hydrochloric acid, and improve the metal ion leaching rate.

[0038] II. Treat the PV ribbon sample with hydrochloric acid to separate the copper strip and the filtrate.

[0039] Place the pretreated PV ribbon sample in a hydrochloric acid solution according to a certain solid-liquid ratio and react at a certain temperature. Among them, the solid-liquid ratio between the PV ribbon sample and the hydrochloric acid solution ranges from 1:10 to 25, the concentration range of the hydrochloric acid solution is 2 - 5 M (1 M represents a concentration of 1 mole per liter), the reaction temperature range is 50 - 70 °C, and the reaction time range is 1 - 3 h. In the experiment, take the filtrate sample once every certain time to separate the copper strip and the filtrate.

[0040] III. Add a hydroxide solution to adjust the pH value of the filtrate obtained in the previous step, and generate hydroxide precipitates of three metals, aluminum, lead, and tin, in sequence at specific pH values from low to high, and separate the precipitates for standby in sequence.

[0041] At the beginning of this step, add a hydroxide solution to adjust the pH value of the filtrate to pH = 5 to generate aluminum hydroxide precipitate and separate the aluminum hydroxide precipitate; then add a hydroxide solution to adjust the pH value of the filtrate to pH = 8 to generate lead hydroxide precipitate and separate the lead hydroxide precipitate; finally, add a hydroxide solution to adjust the pH value of the filtrate to pH = 10 to generate tin hydroxide precipitate and separate the tin hydroxide precipitate.

[0042] The hydroxide solution added is generally a soluble base solution such as sodium hydroxide solution or potassium hydroxide solution. After generating the corresponding metal hydroxide precipitate, centrifugal separation is used to separate the corresponding hydroxide precipitate. The separated metal hydroxide precipitate can be pickled with hydrochloric acid once and washed multiple times to obtain pure metal hydroxide, which is then used for subsequent resource utilization.

[0043] IV. Dissolve the aluminum hydroxide precipitate in dilute hydrochloric acid again to generate aluminum chloride, and extract aluminum chloride as an aluminum-based flocculant after sufficient reaction.

[0044] In this step, dissolve the aluminum hydroxide precipitate in dilute hydrochloric acid again, and the generated aluminum chloride. This reaction is relatively mild and can be carried out at a lower temperature. The reaction equation is Al(OH)3 + 3HCl → AlCl3 + 3H2O. After the reaction is complete, extract the aluminum chloride from the solution and use it as an aluminum-based flocculant.

[0045] V. Dissolve the lead hydroxide precipitate and / or the tin hydroxide precipitate in dilute hydrochloric acid again to generate lead chloride and / or tin chloride respectively. Lead chloride and / or tin chloride are used as lead source and / or tin source respectively, and then react the lead source and / or tin source with organic amine to synthesize the corresponding lead-based perovskite material and / or tin-based perovskite material.

[0046] This step separately processes the lead hydroxide precipitate and the tin hydroxide precipitate. There is no order of precedence between the two and the step four, and they can be processed simultaneously. First, the lead hydroxide precipitate / tin hydroxide is dissolved in dilute hydrochloric acid again, and lead chloride / tin chloride is formed by reaction. Thereafter, lead chloride / tin chloride is extracted as the lead source / tin source, and then the lead source / tin source reacts with an organic amine (such as methylamine CH3NH2) to synthesize the corresponding lead-based / tin-based perovskite structure.

[0047] The preparation methods for the reaction of lead chloride with an organic amine include thermal injection method, microwave method or chemical vapor deposition method. Among them, the microwave method synthesizes micron-scale sheets containing CsPbCl3 nanocrystals, which have appropriate stability in water. First, Cs2CO3 (0.0326 g), PbCl2 (0.1668 g), diethylene glycol butyl ether (5.00 mL), octadecene (5.00 mL), oleic acid (0.50 mL), and oleylamine (0.50 mL) are separately placed in a microwave bottle; then a magnetic stirrer is added and the bottle is placed in a microwave instrument, and micron-scale sheets containing CsPbCl3 nanocrystals are synthesized by a programmed temperature increase method (from room temperature to 150 °C in 3 minutes and then kept warm for 15 minutes); when the sample cools to 71 °C, the microwave bottle is taken out of the microwave instrument, cooled to room temperature with ice water, and centrifuged at 8500 rpm for 8 minutes, and the solid is retained.

[0048] In addition, the tin source can be dissolved in an organic solvent. For example, N,N-dimethylformamide (DMF) or N-methylpyrrolidone (NMP) is used as the organic solvent to dissolve the tin source to obtain a tin precursor solution, and then the precursor solution is used for the reaction with an organic amine. The preparation methods for the reaction of tin chloride with an organic amine include solution method, chemical vapor deposition method, solid-phase method, etc.

[0049] This method has the following specific embodiments.

[0050] Example 1

[0051] (1) The waste photovoltaic panel is manually disassembled or mechanically disassembled to remove the aluminum frame and junction box to obtain a cell module.

[0052] (2) The disassembled cell module is calcined in a muffle furnace at 500 °C for 30 min to obtain silicon wafers and photovoltaic solder tapes.

[0053] (3) The photovoltaic solder tape is processed into small pieces; and 3 g of the solder tape is weighed with an electronic balance.

[0054] (4) The weighed photovoltaic solder tape sample is placed in a 2 M hydrochloric acid solution according to a solid-liquid ratio of 1:10, and reacted at 50 °C for 1 h. After separation, copper is recovered in the form of copper bars.

[0055] During the reaction, samples were taken every 30 minutes to observe the dissolution situation. Each time, 10 mL of the solution was taken out, and a total of 2 samples were taken (0.5 h, 1 h). The filtrate after each sampling was used for the subsequent extraction steps. Since the H+ ions in the hydrochloric acid solution are difficult to oxidize Cu into Cu 2+ , the hydrochloric acid solution has only a slight effect on copper, and copper can be recovered in the form of copper bars. The recovery rate of copper by this treatment method reaches 98%.

[0056] (5) Sodium hydroxide solution was added dropwise to the filtrate after each sampling until the pH value reached 5, forming aluminum hydroxide precipitate. Solid-liquid separation was carried out using a centrifuge, and the precipitate was taken out and washed with distilled water.

[0057] (6) Sodium hydroxide solution was added dropwise to the filtrate after each sampling until the pH value reached 8, forming lead hydroxide precipitate. Solid-liquid separation was carried out using a centrifuge, and the precipitate was taken out and washed with distilled water.

[0058] (7) Sodium hydroxide solution was added dropwise to the filtrate after each sampling until the pH value reached 10, forming tin hydroxide precipitate. Solid-liquid separation was carried out using a centrifuge, and the precipitate was taken out and washed with distilled water.

[0059] Mechanism of action of aluminum chloride flocculant: The flocculation mechanism of aluminum chloride in water treatment mainly depends on its chemical action on suspended solids, colloidal particles and dissolved substances in water. Its action mechanisms include charge neutralization, bridging, coprecipitation and floc growth. Charge neutralization mechanism: After aluminum chloride dissociates in water, aluminum ions meet negatively charged particles in water and undergo a charge neutralization reaction. After the surface charge of the particles disappears, the electrostatic repulsion weakens, and the particles begin to adsorb and aggregate with each other; Bridging mechanism: Aluminum ions in aluminum chloride form bridges with colloidal particles in water through chemical bonds or electrostatic interactions, enabling the particles to adsorb each other and thus aggregate into larger flocs. As the core of the bridge, aluminum ions can connect two or more particles together, prompting them to form large flocs; Coprecipitation mechanism: Aluminum ions generated after aluminum chloride dissociates in water can react with certain dissolved substances in water to form insoluble compounds, which then settle down. This coprecipitation is very effective in removing harmful substances such as heavy metal ions and fluorides in water. Floc growth mechanism: Under appropriate conditions, aluminum chloride can not only promote the aggregation of particles, but also promote the growth of flocs. This growth makes the formed flocs larger, heavier and have a faster sedimentation rate, thus improving the efficiency of water treatment.

[0060] Aluminum-based flocculants are widely used in water treatment, industrial wastewater treatment and other fields to remove suspended solids, colloids and harmful substances in water, and can effectively improve the quality of water.

[0061] Example 2

[0062] The processing method of this embodiment is basically the same as that of Embodiment 1. The differences are that the concentration of the hydrochloric acid solution in step (4) is 3M, the solid-liquid ratio is 1:15, the reaction temperature is 60 °C, and the reaction time is 2h. The copper recovery rate of this processing method reaches 98.4%.

[0063] Embodiment 3

[0064] The processing method of this embodiment is basically the same as that of Embodiment 1. The differences are that the concentration of the hydrochloric acid solution in step (4) is 4M, the solid-liquid ratio is 1:20, the reaction temperature is 70 °C, and the reaction time is 3h. The copper recovery rate of this processing method reaches 99%.

[0065] Embodiment 4

[0066] The processing method of this embodiment is basically the same as that of Embodiment 1. The differences are that in step (4), the solid-liquid ratio of the PV ribbon sample to the hydrochloric acid solution is 1:15, the concentration of the hydrochloric acid solution is 3M, the reaction temperature is 50 °C, the reaction time is 1h, the solution is sampled every 30 minutes, 10 mL of the solution is taken each time, and a total of 2 samplings are taken (0.5h, 1h). The aluminum recovery rates of this processing method are 91% and 92% respectively.

[0067] Embodiment 5

[0068] The processing method of this embodiment is basically the same as that of Embodiment 4. The differences are that in step (4), the solid-liquid ratio of the PV ribbon sample to the hydrochloric acid solution is 1:20, the concentration of the hydrochloric acid solution is 4M, the reaction temperature is 60 °C, the reaction time is 2h, the solution is sampled every 30 minutes, 10 mL of the solution is taken each time, and a total of 4 samplings are taken (0.5h, 1h, 1.5h, 2h). The aluminum recovery rates of this processing method are 91.3%, 92.6%, 93.1%, and 93.5% respectively.

[0069] Embodiment 6

[0070] The processing method of this embodiment is basically the same as that of Embodiment 1. The differences are that in step (4), the solid-liquid ratio of the PV ribbon sample to the hydrochloric acid solution is 1:25, the concentration of the hydrochloric acid solution is 5M, the reaction temperature is 70 °C, the reaction time is 2.5h, the solution is sampled every 30 minutes, 10 mL of the solution is taken each time, and a total of 5 samplings are taken (0.5h, 1h, 1.5h, 2h, 2.5h). The aluminum recovery rates of this processing method are 91.5%, 93%, 93.6%, 94%, and 94.2% respectively.

[0071] Embodiment 7

[0072] The treatment method of this embodiment is basically the same as that of Embodiment 6, except that in step (4), the solid-liquid ratio of the PV ribbon sample to the hydrochloric acid solution is 1:15, the concentration of the hydrochloric acid solution is 3M, the reaction temperature is 60 °C, the reaction time is 2h, the solution is sampled every 30min, 10mL of the solution is taken each time, and a total of 4 samples are taken (0.5h, 1h, 1.5h, 2h). The lead recovery rates of this treatment method are 91.2%, 92.3%, 92.9%, and 93.3% respectively.

[0073] Embodiment 8

[0074] The treatment method of this embodiment is basically the same as that of Embodiment 7, except that in step (4), the solid-liquid ratio of the PV ribbon sample to the hydrochloric acid solution is 1:20, the concentration of the hydrochloric acid solution is 4M, the reaction temperature is 70 °C, the reaction time is 2h, the solution is sampled every 30min, 10mL of the solution is taken each time, and a total of 4 samples are taken (0.5h, 1h, 1.5h, 2h). The lead recovery rates of this treatment method are 91.5%, 92.9%, 93.4%, and 93.9% respectively.

[0075] Embodiment 9

[0076] The treatment method of this embodiment is basically the same as that of Embodiment 7, except that in step (4), the solid-liquid ratio of the PV ribbon sample to the hydrochloric acid solution is 1:25, the concentration of the hydrochloric acid solution is 5M, the reaction temperature is 70 °C, the reaction time is 2h, the solution is sampled every 30min, 10mL of the solution is taken each time, and a total of 4 samples are taken (0.5h, 1h, 1.5h, 2h). The lead recovery rates of this treatment method are 91.8%, 93%, 93.5%, and 94.1% respectively.

[0077] Embodiment 10

[0078] The treatment method of this embodiment is basically the same as that of Embodiment 1, except that in step (4), the solid-liquid ratio of the PV ribbon sample to the hydrochloric acid solution is 1:15, the concentration of the hydrochloric acid solution is 3M, the reaction temperature is 70 °C, the reaction time is 2h, the solution is sampled every 30min, 10mL of the solution is taken each time, and a total of 4 samples are taken (0.5h, 1h, 1.5h, 2h). The tin recovery rates of this treatment method are 90.3%, 91.2%, 92.5%, and 92.7% respectively.

[0079] Embodiment 11

[0080] The processing method of this embodiment is basically the same as that of Embodiment 10, except that in step (4), the solid-liquid ratio of the PV ribbon sample to the hydrochloric acid solution is 1:20, the concentration of the hydrochloric acid solution is 4M, the reaction temperature is 60 °C, the reaction time is 2h, the solution is sampled every 30 minutes, 10 mL of the solution is taken each time, and a total of 4 samples are taken (0.5h, 1h, 1.5h, 2h). The tin recovery rates of this processing method are 90.6%, 91.6%, 93%, and 93.2% respectively.

[0081] Embodiment 12

[0082] The processing method of this embodiment is basically the same as that of Embodiment 10, except that in step (4), the solid-liquid ratio of the PV ribbon sample to the hydrochloric acid solution is 1:25, the concentration of the hydrochloric acid solution is 5M, the reaction temperature is 70 °C, the reaction time is 2h, the solution is sampled every 30 minutes, 10 mL of the solution is taken each time, and a total of 4 samples are taken (0.5h, 1h, 1.5h, 2h). The tin recovery rates of this processing method are 90.8%, 92%, 93.3%, and 93.6% respectively.

[0083] After the above embodiments, a chart showing the experimental results can be obtained, as Figures 2-5 shown. Among them, Figure 2 In the experiment shown, the concentration of the hydrochloric acid solution is set to 5M, the solid-liquid ratio is 1:25, the reaction temperature is 70 °C, and the reaction times are 0.5h, 1h, 1.5h, 2h, and 2.5h respectively. The effect of the reaction time on the aluminum leaching rate is investigated. It can be seen from the figure that under other conditions unchanged, the aluminum leaching rate increases with the increase of the reaction time. When the reaction time is 0.5h, the aluminum leaching rate is 91.5%; when the reaction time is 1.5h, the aluminum leaching rate is 93.6%; when the reaction time is 2.5h, the aluminum leaching rate reaches 94.2%.

[0084] Figure 3 In the experiment shown, the concentration of the hydrochloric acid solution is set to 5M, the solid-liquid ratio is 1:25, the reaction temperature is 70 °C, and the reaction times are 0.5h, 1h, 1.5h, and 2h respectively. The effect of the reaction time on the lead leaching rate is investigated. It can be seen from the figure that under other conditions unchanged, the lead leaching rate increases with the increase of the reaction time. When the reaction time is 0.5h, the lead leaching rate is 91.8%; when the reaction time is 1.5h, the lead leaching rate is 93.5%; when the reaction time is 2h, the lead leaching rate reaches 94.1%.

[0085] Figure 4In the experiment shown, the concentration of the hydrochloric acid solution was set at 5 M, the solid-liquid ratio was 1:25, the reaction temperature was 70 °C, and the reaction times were 0.5 h, 1 h, 1.5 h, and 2 h respectively. The effect of the reaction time on the tin leaching rate was investigated. As can be seen from the figure, under the condition that other conditions remain unchanged, the tin leaching rate increases with the increase of the reaction time. When the reaction time was 0.5 h, the tin leaching rate was 90.8%; when the reaction time was 1.5 h, the tin leaching rate was 93.3%; when the reaction time was 2 h, the tin leaching rate reached 93.6%

[0086] Figure 5 The XRD pattern of the solder ribbon after reaction in hydrochloric acid of 2-6 M in the present invention is shown. The concentrations of the hydrochloric acid solution where the solder ribbon was located were 2 M, 3 M, 4 M, 5 M, and 6 M respectively, the solid-liquid ratio was 1:25, the reaction temperature was 70 °C, and the XRD pattern of the solder ribbon after a reaction time of 2 h. As can be seen from the figure, when the concentration of the hydrochloric acid solution is 5 M, there are fewer miscellaneous peaks, indicating that the solder ribbon reacts more fully, and the leaching effects of metal ions such as aluminum, lead, and tin are the best.

[0087] In addition to PbCl2 and SnCl2, Br- can also be introduced by the complete hydrolysis of the NaBr solution to produce PbBr2 and SnBr2. Among them, PbBr2 and PbCl2 are not only a key lead source for the formation of perovskite materials, but also in some perovskite materials, PbBr2 and PbCl2 can also affect the optoelectronic properties of the final material. Both SnBr2 and SnCl2 can be used to prepare tin-based perovskite materials, which have received extensive attention in the optoelectronic field (especially solar cells and photodetectors) in recent years. Due to the elemental characteristics of tin (such as low toxicity and low atomic valence), tin-based perovskite materials are considered a potential material for environmentally friendly replacement of lead-based perovskites.

[0088] The present invention has been described exemplarily in combination with the accompanying drawings. Obviously, the specific implementation of the present invention is not limited by the above-mentioned manner. As long as various non-substantial improvements are made by adopting the inventive concept and technical solution of the present invention, or the inventive concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A method for recycling metal resources in waste photovoltaic welding ribbons, characterized by: The following steps are involved:

1. Disassembly and calcination of photovoltaic welding ribbons to obtain small block photovoltaic welding ribbon samples; 2. Treat the photovoltaic ribbon samples with hydrochloric acid to separate the copper strips and the filtrate; 3. Adding a hydroxide solution to adjust the pH value of the filtrate obtained in the previous step, generating hydroxide precipitates of aluminum, lead and tin at specific pH values ​​in order from low to high, and separating the precipitates in order for later use; 4. Dissolving the aluminum hydroxide precipitate in dilute hydrochloric acid again to generate aluminum chloride, and extracting the aluminum chloride after sufficient reaction to use as an aluminum-based flocculant; 5. Dissolve the lead hydroxide precipitate and / or the tin hydroxide precipitate in dilute hydrochloric acid again to generate lead chloride and / or tin chloride, use the lead chloride and / or tin chloride as lead source and tin source, respectively, and then react the lead source and / or tin source with organic amine to synthesize the corresponding lead-based perovskite material and / or tin-based perovskite material.

2. The method for recycling metal resources in waste photovoltaic welding ribbons according to claim 1, characterized in that: In step one, the waste photovoltaic panels are first disassembled manually or mechanically to remove the aluminum frame and the junction box to obtain a cell assembly; the disassembled cell assembly is then calcined in a muffle furnace at a certain temperature for a certain period of time to obtain silicon wafers and photovoltaic welding strips; the photovoltaic welding strips are pre-processed into small blocks for subsequent processing.

3. The method for recycling metal resources in waste photovoltaic welding ribbons according to claim 1, characterized in that: In step two, the pretreated photovoltaic ribbon sample is placed in a hydrochloric acid solution according to a certain solid-liquid ratio and reacted at a certain temperature. The solid-liquid ratio between the photovoltaic ribbon sample and the hydrochloric acid solution is in the range of 1:10-25, the concentration of the hydrochloric acid solution is in the range of 2-5M, the reaction temperature is in the range of 50-70°C, and the reaction time is in the range of 1-3h.

4. The method for recycling metal resources in waste photovoltaic welding ribbons according to claim 1, characterized in that: In step 3, the pH value of the filtrate is adjusted to pH=5 to generate aluminum hydroxide precipitate, and the aluminum hydroxide precipitate is separated; the pH value of the filtrate is adjusted to pH=8 to generate lead hydroxide precipitate, and the lead hydroxide precipitate is separated; the pH value of the filtrate is adjusted to pH=10 to generate tin hydroxide precipitate, and the tin hydroxide precipitate is separated.

5. The method for recycling metal resources in waste photovoltaic welding ribbons according to claim 1, characterized in that: In step three, the hydroxide precipitates of aluminum, lead and tin are separated from the filtrate by centrifugal separation. The separated metal hydroxide precipitates can be further washed with hydrochloric acid once and multiple times.

6. The method for recycling metal resources in waste photovoltaic welding ribbons according to claim 3, characterized in that: In step 2, during the reaction process, samples were taken every 30 minutes to observe the dissolution, 10 mL of solution was taken out each time, and a total of 2-5 samples were taken.

7. The method for recycling metal resources in waste photovoltaic welding ribbons according to claim 2, characterized in that: In step 1, the calcination temperature is 500° C., the calcination time at 500° C. is 30 min, the heating time is set to 100 min, and the heating rate is 5° C. / min.

8. The method for recycling metal resources in waste photovoltaic welding ribbons according to claim 1, characterized in that: In the step 5, the preparation method of the reaction of lead chloride and organic amine includes a microwave method, firstly, Cs2CO3, PbCl2, diethylene glycol butyl ether, octadecene, oleic acid, and oleylamine are respectively placed in a microwave bottle; then, a stirring bar is added and the bottle is placed in a microwave instrument, and a programmed temperature method is used to synthesize micron flakes containing CsPbCl3 nanocrystals; when the sample is cooled to 71°C, the microwave bottle is taken out of the microwave instrument, cooled to room temperature with ice water, and the solid is retained after centrifugation.